Optimalisasi Peran Desa Wisata Pesisir Sumenep untuk Peningkatan Kesejahteraan Ekonomi Masyarakat - A. Yahya Surya Winata; Qoni'ah Nur Wijayani; Ana Tsalitsatun Ni'mah (Universitas Trunodjoyo Madura, 2025)
The development of tourist villages is an effective strategy to enhance the economic welfare of communities, particularly in coastal areas rich in natural and cultural potential. This article discusses a community service program focused on optimizing tourist villages in the coastal areas of Sumenep. The activities include training on tourism management, empowering local communities through tourism-based skill development, digital promotion, and strengthening economic institutions such as Village-Owned Enterprises (BUMDes). The results indicate an increase in the community's capacity to manage tourism potential, a rise in the number of tourist visits, and a positive impact on the local community's income. Through strong collaboration among the community, government, and relevant stakeholders, optimizing tourist villages can create a sustainable tourism ecosystem while supporting the welfare of coastal communities in Sumenep.